2011
DOI: 10.1074/jbc.m110.163865
|View full text |Cite|
|
Sign up to set email alerts
|

HDAC3-dependent Reversible Lysine Acetylation of Cardiac Myosin Heavy Chain Isoforms Modulates Their Enzymatic and Motor Activity

Abstract: Reversible lysine acetylation is a widespread post-translational modification controlling the activity of proteins in different subcellular compartments. We previously demonstrated that a class II histone deacetylase (HDAC), HDAC4, and a histone acetyltransferase, PCAF, associate with cardiac sarcomeres, and a class I and II HDAC inhibitor, trichostatin A, enhances contractile activity of myofilaments. In this study, we show that a class I HDAC, HDAC3, is also present at cardiac sarcomeres. By immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 32 publications
2
37
0
Order By: Relevance
“…In an interesting model, Jackson [101] discussed the possible role of N-terminal acetylation of GTPases, and subsequent association of this enzyme with membrane, a process that further influences membrane trafficking and organelle structure in eukaryotic cells. Cytoskeletal proteins such as cytokeratins [102], tubulin [103][104][105] and myosin [99,106] can also be acetylated, and this PTM can influence their association with the plasma membrane. Casale et al [103] and Santander et al [104] have shown that the brain plasma membrane Na 1 , K 1 -ATP-ase is inhibited by acetylated tubulin.…”
Section: Acetylationmentioning
confidence: 99%
“…In an interesting model, Jackson [101] discussed the possible role of N-terminal acetylation of GTPases, and subsequent association of this enzyme with membrane, a process that further influences membrane trafficking and organelle structure in eukaryotic cells. Cytoskeletal proteins such as cytokeratins [102], tubulin [103][104][105] and myosin [99,106] can also be acetylated, and this PTM can influence their association with the plasma membrane. Casale et al [103] and Santander et al [104] have shown that the brain plasma membrane Na 1 , K 1 -ATP-ase is inhibited by acetylated tubulin.…”
Section: Acetylationmentioning
confidence: 99%
“…However, it is important to emphasize that this is an oversimplification. For example, HDAC3 has also been found at the plasma membrane, where it regulates Src tyrosine kinase activity [21], and in cardiomyocytes HDAC3 has been shown to co-localize with sarcomeres [22]. …”
Section: Class I Hdacs and Cardiac Signaling And Gene Expressionmentioning
confidence: 99%
“…Taken together, these studies support that excessive activation of p300 acetyltransferase is involved in pathologic cardiac hypertrophy and inhibition of p300 might be a potential therapeutic strategy in HF. While p300 has been the most extensively studied, other proteins with Kac ”writing” capabilities such as CBP and PCAF are also emerging as important regulators of cardiac remodeling 85 .…”
Section: Histone Ptms - Lysine Acetylationmentioning
confidence: 99%
“…A number of these HDACs have been studied in the context of cardiac remodeling and HF pathogenesis using genetically modified mouse models and pharmacological inhibitors 46, 85, 87-111 (Table 2). Of these, members of HDAC classes I, IIa, and III have been most extensively studied while very little is known about class IIb and IV HDACs.…”
Section: Histone Ptms - Lysine Acetylationmentioning
confidence: 99%
See 1 more Smart Citation